Islamic Religious Education Learning Design with Models Analysis, Design, Development, Implementation and Evaluation (ADDIE) - Hidayat Aji Permana; Uus Ruswandi; Yeti Heryati (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2022)
This journal aims to find out the design of Islamic religious education learning with the ADDIE model, therefore there are several learning designs, one of which is instructional. In the learning system there is a generic model. One of them is the ADDIE generic model system. The model has to do with learning Islamic religious education. The research method uses a qualitative approach with library research. ADDIE is a generic model that can be applied in education. ADDIE itself is the acronym of Analysis, Design, Development, Implementation and Evaluation which can be applied procedurally, cyclically and integratively. The approach used is ADDIE Procedural, the goal is to require an educator to take steps in sequence. Learning Islamic Religious Education can be known progress and well-validated learning because of the steps that have been well structured.